முதுநிலைத் தமிழ்ப் பாடநூல் - Pon Subbaiah (My University, 2010)
The main course material to be used at the advanced level of the 10-month intensive program is meant for the Non-Tamils learning Tamil as L2; the objective is to highlight the free usage of structures, stylistic variations, and the dialects of Tamil being a language of diglossia; it is achieved through a compendium of carefully identified graded samples of 12 prose pieces, 18 poetic compositions, and 7 categories of specialized practical usages.
Advanced Course Reader in Tamil (Revised) Re-print
Keywords: Tamil